1990
DOI: 10.4319/lo.1990.35.1.0045
|View full text |Cite
|
Sign up to set email alerts
|

Pigments, size, and distributions of Synechococcus in the North Atlantic and Pacific Oceans

Abstract: Dual-beam flow cytometry was used to analyze the distribution and optical characteristics of Synechococcus in the North Atlantic and Pacific Oceans. The depth range over which Synechococcus cells were abundant was related to the depth of the nitrite maximum and the chlorophyll maximum, but was not significantly correlated with the depth of the surface isothermal layer. Dual-beam analysis of chromophore pigment types revealed that the majority of the populations were of the high-urobilin type; low-urobilin type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
212
4
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(236 citation statements)
references
References 25 publications
18
212
4
2
Order By: Relevance
“…Two prokaryotic cyanobacteria, Prochlorococcus marinus (Chisholm et al, 1988;Partensky et al, 1999) and Synechococcus spp. (Waterbury et al, 1979(Waterbury et al, , 1986Olson et al, 1990;Li, 1998;Bertilsson et al, 2003;Heldal et al, 2003) belong to the most thoroughly investigated algal species of the pico-phytoplankton community. Only a very limited number of eukaryotic pico-phytoplankton species have been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Two prokaryotic cyanobacteria, Prochlorococcus marinus (Chisholm et al, 1988;Partensky et al, 1999) and Synechococcus spp. (Waterbury et al, 1979(Waterbury et al, , 1986Olson et al, 1990;Li, 1998;Bertilsson et al, 2003;Heldal et al, 2003) belong to the most thoroughly investigated algal species of the pico-phytoplankton community. Only a very limited number of eukaryotic pico-phytoplankton species have been investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the open ocean, only the high-PUB type has been found. The dominant Synechococcus in the North Atlantic and East Pacific Oceans was the high-PUB type 7,8) . Campbell and Vaulot (1993) showed that only the high-PUB type was detected at a station off Hawaii.…”
Section: Discussionmentioning
confidence: 99%
“…6c). Olson et al (1990) reported that the low-PUB type was detected at 40 out of 81 stations in coastal seas, and that 34 out of these 40 stations had both low-and high-PUB types. In the Arabian Sea, low-PUB types were more abundant at coastal stations 3) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations